Reducing poverty through agricultural sector strategies in Eastern and Southern Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Full proceedings of a workshop, Wageningen, the Netherlands, 23-25 November 1998.EC and CTA, 1999. 96 pp.ISBN 92 9081 2125CTA No 938, 10 credit points